Comparative study of hematological and blood chemistry of Persian sturgeon (Asipencer persicus) exposed to two common anticoagulants - GHOLIPOURKANANI, H.; RANJDOOST, M.; JAFARYAN, H.; YELGHI, S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The effects of heparin and ethylenediaminetetraacetic acid (EDTA) on plasma biochemistry and hematological parameters in Asipencer persicus were studied. Differences in ALT and ALP activity were found between serum and heparinized plasma (P<0.05). AST activity in EDTA treated samples increased (P<0.05) compared to its values in serum. On the contrary, ALP activity showed a significant decrease compared to its serum level (P<0.05). Samples collected with EDTA showed an increase in haematocrit, mean corpuscular volume (MCV) and white blood cells (WBC) values (P<0.05) when compared to those collected in heparin. The other measured biochemical parameters did not show any variation. The present study suggests the use of heparin as a preferred anticoagulant for routine haematological analyses in the Persian sturgeon. However, both of these anticoagulants inflicted changes in selected biochemical parameters.